Identifikasi Unsur Penyusun Sedimen Sungai Klagison Kota Sorong Papua Barat Daya Menggunakan Metode X-Ray Fluorescence (XRF) - Nurbia, Nurbia; Affandi, Samsudin (Jurnal Teknologi Lingkungan Lahan Basah, 2024)
The Klagison River is one of the rivers in Sorong City, West Papua. Surface mining activities occur in the Klagison River drainage area which is one of the causes of changes in the geomorphological conditions of the Klagison River. to identify the constituent elements of the Klagison River sediment using X-Ray Fluorescence (XRF). Determination of sampling points using the purposive sampling method and sediment collection tools using the Ekman grab. The method for analyzing sediment constituent elements uses the XRF (X-Ray Fluorescence) method. Based on the research results, there are various types of elements contained in the Klagison River sediment, namely the elements Al, Si, P, S, Cl, K, Ca, Ti, V, Cr, Mn, Fe, Ni, Cu, Zn, Rb, Sr, Zr and Re. The dominant metal element concentrations from the 5 observation stations are the elements FeSiClAlCaTi. At observation station 5, the elements FeSiClAlCaTi are highest compared to the other 4 observation stations, this is because station 5 is the estuary of the Klagison River so it is the last place where liquid waste settles